341 Surgical morbidity of laparoscopic vs. open surgery for Borderline Ovarian Tumors: a single center analysis. (13th November 2020) - Oltolina, N; Longo, M; Lembo, A; Dri, M; La Motta, G; Granato, V; Ghezzi, F; Casarin, J
Abstract : Objective: To evaluate the short-term morbidity in Borderline Ovarian Tumor (BOT) patients who underwent laparoscopic (LPS) vs. open abdominal laparotomic (LPT) surgery. Methods: We retrospectively analyzed data of consecutive patients treated for primary diagnosis of apparent early stage BOT at Del Ponte Hospital (Varese–Italy) between January 2004 and December 2019. Both radical and fertility-sparing treatments were included in our investigation. Demographic characteristics, operative outcomes and 30-day complications were evaluated and compared between the two surgical approaches. Results: We included data of 128 patients, 84 LPS and 44 LPT. Fifty-seven patients underwent fertility sparing surgery (LPS=31, LPT=26) while 71 patients underwent radical treatment (LPS=53, LPT=18, p=0, 17). When comparing LPS vs LPT, median age at surgery was 45, 5 vs 59 years old (p<0.001), with 38, 09% vs 59, 9% patients in menopausal status, respectively (p=0, 02). Ten (11, 9%) and 14 (31, 81%) patients had previous open abdominal/pelvic surgery in the LPS and LPT groups, respectively (p=0, 0061). Charlson Comorbidity Index >3 was found in 5 (5, 95%) vs. 15 (34, 1%) patients (P=0, 002). No significant differences were found in terms of parity, previous Caesarean section, previous minimally invasive abdominal/pelvic surgery, and race. Regarding the short-term morbidity, LPS was associated with less blood loss (50 ml vs 200 ml, p=0, 01), need for perioperative blood transfusions (0% vs. 6, 82%, p=0, 005) and in-hospital complications (0% vs. 4, 55%, p=0, 04). Conclusions: Because of the favorable surgical outcomes, LPS should be considered the standard surgical approach for the treatment of patients with primary diagnosis of early stage BOT.